Fieldwork in Social Work Education and Training: Issues and Challenges in the Case of Eastern and Southern Africa - Jotham Dhemba (Social Work and Society)
While it is widely accepted that fieldwork and its theory counterpart in social work education are of equal importance, the fieldwork component is marginalised at some social work training institutions in Eastern and Southern Africa. This study, which was carried out at three selected social work training institutions involved gathering data from social work students, agency supervisors and fieldwork coordinators using personal interviews and questionnaires. The study found that there are practices at these institutions that inadvertently diminish its importance. Such practices include the use of non-social work agency supervisors, lack of training for agency supervisors, the lack of a fieldwork curriculum and non-existent or inadequate funding of fieldwork related activities. It is quite clear that inadequate funding is the root cause of most of the challenges bedeviling fieldwork and that fieldwork shall remain just a ritual if this situation is not addressed.